Impact of intragastric administration of donkey milk on mouse immunity utilizing gut microbiomics and plasma metabolomics - Wang, Jianwen; Ren, Wanlu; Sun, Zhiwen; Liu, Shibo; Han, Zixiang; Wang, Yongfa; Zeng, Yaqi; Meng, Jun; Yao, Xinkui (Frontiers in Veterinary Science, 2025)
IntroductionDonkey milk demonstrates closer compositional resemblance to human milk compared to bovine milk, positioning it as an optimal nutritional substitute for infants with cow's milk allergy. Furthermore, its rich profile of bioactive compounds suggests potential immunomodulatory properties. This study systematically investigated the effects of donkey milk supplementation on murine immune function and gut microbiome dynamics, thereby providing mechanistic insights to support its clinical development in functional food applications.MethodsFollowing daily intragastric administration of 10 mL/kg of body weight of donkey milk (DM) or distilled water (DW) to the mice for 28 consecutive days, liver tissues were harvested for immunological profiling, with concurrent collection of blood samples for plasma metabolomic analysis and fecal specimens for gut microbiome characterization. Subsequently, the modulatory effects of donkey milk supplementation on immune parameters, intestinal microbiota composition, and plasma metabolic profiles were systematically evaluated.ResultsImmunity analysis revealed that intragastric administration of DM raised the levels of IL-6 and TNF-α cytokines in mouse liver. In addition, DM modulated the composition of both the murine gut microbiome and plasma metabolites. One-hundred and forty-five differentially-produced metabolites were identified, most prominently nicotinamide, L-valine, and β-estradiol, that are primarily associated with valine, leucine, and isoleucine biosynthesis and degradation, nicotinate and nicotinamide metabolism, and unsaturated fatty acid biosynthesis. Alterations at phylum, genus, and species levels were evident in the fecal microbiota of mice after intragastric administration of DM. In particular, an increased abundance of the Lactobacillus bacterium was observed. Correlation analysis of differential metabolites and microbiomes indicated a correspondence between Falsiroseomonas and Salipiger species and the antioxidant coenzyme Q that has the potential to activate the immune system.ConclusionThe data collectively suggest that DM may adjust the murine gut microbiome and plasma metabolites thereby potentially improving immunity in mice.